2023
DOI: 10.1021/acs.est.2c08960
|View full text |Cite
|
Sign up to set email alerts
|

Emission of Per- and Polyfluoroalkyl Substances from a Waste-to-Energy Plant─Occurrence in Ashes, Treated Process Water, and First Observation in Flue Gas

Abstract: Per- and polyfluoroalkyl substances (PFASs) are a large group of compounds commonly used as industrial chemicals and constituents of consumer products, e.g., as surfactants and surface protectors. When products containing PFASs reach their end of life, some end up in waste streams sent to waste-to-energy (WtE) plants. However, the fate of PFASs in WtE processes is largely unknown, as is their potential to enter the environment via ash, gypsum, treated process water, and flue gas. This study forms part of a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The FBF followed similar trends, but the measurements of the shorter chain PFCA compounds in the stack were not useable due to contamination. Björklund et al (2023) found PFBA to be the most abundant PFAS detected in stack samples from a municipal solid waste (MSW) incinerator while processing MSW alone or when co‐processing dewatered wastewater sludge. Unfortunately, PFBA and PFPeA analyses can be compromised by interferences (Bangma et al, 2023), so results reported here must be viewed with some skepticism until the previously noted nontargeted analyses are completed.…”
Section: Discussionmentioning
confidence: 99%
“…The FBF followed similar trends, but the measurements of the shorter chain PFCA compounds in the stack were not useable due to contamination. Björklund et al (2023) found PFBA to be the most abundant PFAS detected in stack samples from a municipal solid waste (MSW) incinerator while processing MSW alone or when co‐processing dewatered wastewater sludge. Unfortunately, PFBA and PFPeA analyses can be compromised by interferences (Bangma et al, 2023), so results reported here must be viewed with some skepticism until the previously noted nontargeted analyses are completed.…”
Section: Discussionmentioning
confidence: 99%
“…The lowest PFAS values were detected for the pyrolyzed products which is also in good agreement with previous studies. 55,56 However, it has to be kept in mind that thermal treatment of PFAS containing fertilizers may produce volatile ultrashortchain PFAS 57,58 or organouoride compounds like CF 4 , CHF 3 etc. 59 which have a high global warming potential, and may aerwards enter the atmosphere, depending on the used lter systems in thermal treatment plants.…”
Section: Discussionmentioning
confidence: 99%
“…Condensate, boiler ash, and filter ash were collected and pooled on three occasions per sampling day (Table S2). Flue gas was sampled before the wet flue gas cleaning (Figure ) using the EN 1948:1 cooled probe sampling train (Figure S1), which was modified with additional features from air-sampling methodologies described elsewhere . Sludge from the internal water treatment was not accessible at the time of sample collection.…”
Section: Methodsmentioning
confidence: 99%
“…Sample preparation has been described in detail elsewhere. , Briefly, boiler ash and filter ash were weighed into a polypropylene tube and spiked with 3 ng internal standard. To each tube, 5 mL of methanol was added before vortexing for 10 s. Thereafter, samples were ultrasonicated for 15 min before being centrifuged for 10 min at 1200 g .…”
Section: Methodsmentioning
confidence: 99%